Development of multifunctional fluorescence-emitting potential theranostic agents for Alzheimer's disease - Bajad N.G.; T.A G.; Kothari M.; Mukherjee R.; Chowdhury A.; Kumar A.; Krishnamurthy S.; Singh S.K. (My University, 2025)
The cholinergic deficits and amyloid beta (Aβ) aggregation are the mainstream simultaneously observed pathologies during the progression of Alzheimer's disease (AD). Deposited Aβ plaques are considered to be the primary pathological hallmarks of AD and are contemplated as promising diagnostic biomarker. Herein, a series of novel theranostic agents were designed, synthesised and evaluated against cholinesterase (ChEs) enzymes and detection of Aβ species, which are major targets for development of therapeutics for AD. Among all the tested compounds against ChEs enzymes, compound/probe 39 & 43 exhibited potent inhibitory activities. Its excellent BBB permeability was anticipated in PAMPA assay. Measurement of fluorescent properties showed emission maxima (λemm) in between 530 and 550 nm in distinct organic solvent except in the most polar solvent i.e., PBS (10 % DMSO), where broad absorption (λabs of 440 nm) and emission spectrum (λemm of 640 nm) was observed. The relative fluorescence quantum yield of probe 39 in methanol was found to be 0.17. The increase in fluorescence intensity displayed by the probe 39 upon binding with Aβ aggregates in the in vitro assay, and produced high apparent binding constant. Further, it's binding affinity towards Aβ1-42 aggregates was validated on the basis of colocalization with thioflavin T (ThT). A significant enhancement in the fluorescence lifetime of probe 39 on binding with Aβ aggregates was observed in time-correlated single-photon counting (TCSPC) analysis (10.00 ± 1.12 ns) and fluorescence lifetime imaging microscopy (FLIM) imaging (11.53 ± 0.01 ns). Furthermore, acute oral toxicity studies signified the safety profile of lead probe 39. The in-vivo behavioural studies demonstrated a substantial improvement of cognitive and special memory impairment in the scopolamine-induced cognitive deficit in mice model on the administration of compound 39 at a dose of 20 mg/kg. The AChE inhibitory potential and antioxidant property of lead probe 39 were further accessed with ex vivo biochemical analysis. Together, our findings suggest Probe 39 as a promising theranostic agent for the AD. © 2025 Elsevier B.V.